DAPATKAH INTELLECTUAL CAPITAL MEMPENGARUHI HARGA SAHAM - Supriadi, Adi (LAND JOURNAL, 2026)
This study aims to examine and analyze the influence of Sales Growth and Intellectual Capital on Stock Prices in non-cyclical consumer companies listed on the Indonesia Stock Exchange for the period 2023 to 2025. This type of research is quantitative research, using secondary data. The data analysis method used is a panel data regression test using the Eviews 12 application. The population in this study is all non-cyclical consumer sectors listed on the Indonesia Stock Exchange for the period 2023 to 2025. The data collection technique in this study was a purposive sampling technique with results from 105 companies with certain criteria obtained as many as 35 companies. The results of the study show that Sales Growth and Intellectual Capital together can affect stock prices and Intellectual Capital has a significant effect on Stock Prices. This increase in sales provides a positive signal to investors that the company has good growth prospects, which can increase investor interest in buying the company's shares. Conversely, if the results are negative, this indicates a decrease in sales that can reduce investor interest. The results of intellectual capital, namely Intellectual capital, reflect the company's ability to manage intangible assets to create value. A high score on intellectual capital indicates that the company has successfully optimized the use of physical capital, human resources, and organizational structure to increase added value.